Design of Reconfigurable Logic Controllers - Karatkevich, Andrei; Bukowiec, Arkadiusz; Doligalski, Michał; Tkacz, Jacek; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents the original concepts and modern techniques for specification, synthesis, optimisation and implementation of parallel logical control devices. It deals with essential problems of reconfigurable control systems like dependability, modularity and portability. Reconfigurable systems require a wider variety of design and verification options than the application-specific integrated circuits. The book presents a comprehensive selection of possible design techniques. The diversity of the modelling approaches covers Petri nets, state machines and activity diagrams. The preferences of the presented optimization and synthesis methods are not limited to increasing of the efficiency of resource use. One of the biggest advantages of the presented methods is the platform independence, the FPGA devices and single board computers are some of the examples of possible platforms. These issues and problems are illustrated with practical cases of complete control systems. If you expect a new look at the reconfigurable systems designing process or need ideas for improving the quality of the project, this book is a good choice.
Petri Nets in Design of Control Algorithms -- Synthesis and Implementation of Parallel Logic Conrollers in All Programmable Systems-on-Chip -- Circuit Implementation of Parallel Logical Control Algorithms Represented in PRALU Description -- Effective Partial Reconfiguration of Logic Controllers Implemented in FPGA Devices -- An Application of Logic Controller for the Aerosol Temperature Stabilization -- Symbolic Coloring of Petri Nets -- Modular Synthesis of Petri Nets -- Architectural Synthesis of Petri Nets -- Decomposition-Based Methods for FSM Implementation -- Using UML Behavior Diagrams for Graphical Specification of Programs for Logic Controllers -- Various Interpretations of Actions of UML Activity Diagrams in Logic Controller Design -- Model Checking of UML Activity Diagrams Using a Rule-Based Logical Model -- UML Support for Statecharts-Based Digital Logic Controller Design in FPGA Technology. .
Keywords: Electronic circuits; Computational intelligence; Control engineering; Electronic Circuits and Systems; Computational Intelligence; Control and Systems Theory